2002
DOI: 10.1152/ajpendo.00412.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increased synthesis rate of fibrinogen as a basis for its elevated plasma levels in obese female adolescents

Abstract: Increased concentrations of plasma fibrinogen, an independent risk factor for cardiovascular disease (CVD), in obese children have been reported. The underlying mechanism for this, however, remains to be defined. In the current study, we measured the fractional synthesis rates (FSR) of plasma fibrinogen in six healthy postpubertal obese girls [body mass index (BMI) 36.6 ± 1.8 kg/m2; age 16.6 ± 0.5 yr] and six age-matched lean normal control girls (BMI 20.8 ± 0.7 kg/m2; age 16.4 ± 0.4 yr) during a primed, conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
4
14
2
1
Order By: Relevance
“…Of note, the magnitudes of change (D-drop) in the FSR of fibrinogen and its concentration were closely correlated. The higher baseline FSR of fibrinogen in obese vs. lean children (both genders) in the current study was similar to the data from an unrelated study in only female adolescents [25]. Volpi et al…”
Section: Discussionsupporting
confidence: 90%
“…Of note, the magnitudes of change (D-drop) in the FSR of fibrinogen and its concentration were closely correlated. The higher baseline FSR of fibrinogen in obese vs. lean children (both genders) in the current study was similar to the data from an unrelated study in only female adolescents [25]. Volpi et al…”
Section: Discussionsupporting
confidence: 90%
“…The apparent insulin resistance observed in the obese subjects in the current study further indicates that the increased protein turnover in obese adolescents is a sign of insulin resistance as reported in previous studies 4,10,40 and suggests a defective suppression of WBPT in obese adolescents. Previous studies have also suggested that the greater peripheral hyperinsulinemia present in obesity could contribute to insulin resistance with respect to proteolysis as well as glucose disposal.…”
Section: Discussionsupporting
confidence: 88%
“…In this respect, it has been demonstrated that most overweight children become obese adults. 22 Indeed, childhood overweight has been shown to produce an adverse risk factor profile during adulthood. 21 -23 Subsequently, the critical duration of exposure to these risk factors may accumulate at an earlier time point, resulting in premature signs of cardiovascular disease.…”
Section: 17 -21mentioning
confidence: 99%